APLIKASI SIX SIGMA SEBAGAI STRATEGI PENINGKATAN KEPUASAN PELANGGAN PENDIDIKAN - Aqillla, Lutfia; Sohiron, Sohiron (STKIP Pesisir Selatan, 2026)
Improving the quality of educational services is a crucial factor inbuilding customer trust and satisfaction, particularly amidstincreasingly fierce competition among educational institutions. Onestrategy proven effective in improving service quality is theimplementation of Six Sigma, a data-driven quality managementapproach that focuses on controlling variation and reducing processerrors. This study aims to analyze the implementation of Six Sigma asa strategy for improving educational customer satisfaction through aliterature review of various previous studies. The current CriticalAnalysis approach addresses the relationship between Six Sigma,quality management, and customer satisfaction in the educationsector. The study results indicate that Six Sigma implementation canimprove institutional operational efficiency, improve academicadministration systems, and increase the level of satisfaction ofstudents and the public using educational services. Furthermore, thesuccess of Six Sigma implementation is influenced by organizationalcommitment, human resource competency, and integration withinternal quality assurance systems. Therefore, it can be concluded thatSix Sigma is a relevant and effective strategy in creating a culture ofquality and increasing educational customer satisfaction sustainably.